Level of physical activity and body image in Portuguese and French students, 1st year of Physiotherapy - Baptista, A. (2021)
Adolescents have a physiological need to move, therefore physical activity should be encouraged at an early age. In young adults, there are also various physical and psychological transformations. Associated with these transformations, there is a will to fit in the patterns of society’s beauty and, sometimes, a consequent bodily dissatisfaction. Thus, it is necessary to encourage physical activity, for its benefits.